RESILIENCE TO FLOURISHING: EXAMINING THE MEDIATING MECHANISM OF FUTURE ORIENTATION IN CHINESE PRESERVICE TEACHERS - Xing, Yi; Siaw , Yan-Li; Loh , Sau-Cheong; Li , Shu Xian; Rashid, Md Harun (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2025)
Objectives: This study examined the psychological mechanisms linking resilience and flourishing among Chinese preservice teachers, a group that experiences substantial stress during the transition from academic training to the professional teaching environment. The objective was to determine whether future orientation functions as a mediating pathway connecting resilience to flourishing. Methods: Using a cross-sectional survey of 352 preservice teachers, partial least squares structural equation modelling (PLS-SEM) was employed to evaluate both the measurement and structural models. Results: Results showed that the model fit was acceptable (SRMR = 0.069) and revealed significant positive direct effects between resilience and future orientation (β = 0.547, T = 13.772, p < 0.000), resilience and flourishing (β = 0.235, T = 4.201, p < 0.000), and future orientation and flourishing (β = 0.456, T = 8.974, p < 0.000). Future orientation also exerted a significant partial mediating effect on the resilience–flourishing relationship (β = 0.249, T = 7.012, p < 0.000). These findings indicate that resilience promotes goal-directed planning and optimistic thinking, which subsequently enhance flourishing. Conclusions: Conceptually, the study extends psychological capital and well-being theories within a collectivist Chinese context, and practically, it offers an evidence-based foundation for teacher education programs that aim to strengthen preservice teachers’ well-being by integrating resilience-building with future-oriented goal-setting training.